Penentuan Kerugian Keuangan Negara Akibat Penyalahgunaan Kewenangan Pejabat Pemerintah - Ridho Mubarak; Wessy Trisna (Universitas Medan Area, 2021)
This study aims to determine that governance must be based on the principle of legality, the principle of protection of human rights and the general principles of good governance (AAUPB), and must be guided by the principle of not abusing authority. Regarding the actions of the authorities for criminal acts of corruption, it can be seen in Article 3 of the Anti-Corruption Law that the authority by someone who has a position or position as a result is detrimental to the State Finance. The research method used is normative legal research with analytical descriptive nature. The research data sources consist of primary and secondary legal sources using a library research approach which are then analyzed qualitatively. The results of the study indicate that the authorities, both according to state administrative law or criminal law, have their respective legal domains, even though both have a close relationship. In terms of the government's accountability for state finances in accordance with Article 30-32 of Law No. 17 of 2003 concerning State Finances, it is stated that both the President and Regional Heads (Governor/Regent/Mayor) are required to submit an accountability report on the implementation of the APBN/APBD to the DPR/DPRD in the form of financial statements that have been audited by the BPK so that it causes state financial losses in corruption in practice more than real losses (actual losses) and does not discuss detrimental losses from potential future losses